Effect of Intermittent Fasting on Non-Alcoholic Fatty Liver Disease: Systematic Review and Meta-Analysis - Yin, Cong; Li, Zihan; Xiang, Yulin; Peng, Hongbing; Yang, Ping; Yuan, Shijun; Zhang, Xueyan; Wu, You; Huang, Min; Li, Juan (Frontiers in Nutrition, 2021)
Abstract Background: Weight loss by lifestyle modification is the cornerstone therapy of non-alcoholic fatty liver disease. Intermittent fasting has shown favorable effects on body weight and relevant indicators of non-alcoholic fatty liver disease in several reports. Objective: Estimate the effects of intermittent fasting on non-alcoholic fatty liver disease adults. Materials and Methods: Literature searches were conducted on PubMed, EMBASE, Web of Science, Cochrane Library, and ClinicalTrials.gov from inception to May 10, 2021. Results: A total of 6 studies involving 417 non-alcoholic fatty liver disease patients were included. In the meta-analysis, there were significant differences in body weight, body mass index, alanine aminotransferase, and aspartate transaminase between the control and fasting group. Still, there was no significant difference in triglycerides, total cholesterol, and other metabolic parameters between the two groups. Conclusion: Intermittent fasting is beneficial for weight management and liver enzyme improvement, but long-term feasibility and safety of the intermittent fasting should be conducted in further study.